2020
DOI: 10.1111/oik.07835
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of a meta‐network to alternative habitat loss scenarios

Abstract: Studying how habitat loss affects the tolerance of ecological networks to species extinction (i.e. their robustness) is key for our understanding of the influence of human activities on natural ecosystems. With networks typically occurring as local interaction networks interconnected in space (a meta-network), we may ask how the loss of specific habitat fragments affects the overall robustness of the meta-network. To address this question, for an empirical meta-network of plants, herbivores and natural enemies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…This may also be true in networks with long distance dispersal, as the ability to colonise habitats further away (rather than the nearest patches only as in this study) has been shown to increase the extinction thresholds (Gawecka and Bascompte, 2021). Finally, we postulate that network rewiring (which has not been considered here for simplicity) may further buffer the effects of habitat loss on both the ecological and coevolutionary dynamics, as the flexibility of interaction partners may increase species' persistence (e.g., Kaiser-Bunbury et al, 2010;Ramos-Jiliberto et al, 2012;Tylianakis and Morris, 2017;Santos et al, 2021).…”
Section: Discussionmentioning
confidence: 56%
“…This may also be true in networks with long distance dispersal, as the ability to colonise habitats further away (rather than the nearest patches only as in this study) has been shown to increase the extinction thresholds (Gawecka and Bascompte, 2021). Finally, we postulate that network rewiring (which has not been considered here for simplicity) may further buffer the effects of habitat loss on both the ecological and coevolutionary dynamics, as the flexibility of interaction partners may increase species' persistence (e.g., Kaiser-Bunbury et al, 2010;Ramos-Jiliberto et al, 2012;Tylianakis and Morris, 2017;Santos et al, 2021).…”
Section: Discussionmentioning
confidence: 56%
“…It was contrary to our expectations that more specific parasitoids comprise more of the metanetwork core than generalists, given that generalists are more frequently encountered due to greater niche breadth (Kassen, 2002; Robinson & Strauss, 2018). Several studies have highlighted the importance of rare or unique parasitoids in stabilising metanetworks (Santos et al, 2020), but the importance of more specific parasitoids in our analyses of metanetwork interactions warrants further study. Moreover, more abundant hosts may support more specialist parasitoids due to the stability of hosts as a resource and sensitivity of specialist parasitoids to fluctuations in host populations (Cagnolo et al, 2009; Holzchuh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such network rewiring has been shown to change network structure (Loeuille & Loreau, 2005; Suweis et al, 2013), and this is expected to alter the eco‐evolutionary dynamics. We postulate that interaction rewiring may buffer the effects of habitat loss, as the flexibility of interaction partners may increase species' persistence (Kaiser‐Bunbury et al, 2010; Ramos‐Jiliberto et al, 2012; Santos et al, 2021; Tylianakis & Morris, 2017).…”
Section: Discussionmentioning
confidence: 99%